State control over private military and security companies in armed conflict - Tonkin, Hannah (Cambridge studies in international and comparative law, 2011)
The past two decades have witnessed the rapid proliferation of private military and security companies (PMSCs) in armed conflicts around the world, with PMSCs participating in, for example, offensive combat, prisoner interrogation and the provision of advice and training.